Dehidrasi N-Butanol menjadi senyawa butena pada katalis molecular sieve 13X dalam reaktor unggun tetap - Melia Laniwati Gunawan; Hendrik Susanto (Jurnal Teknik Kimia Indonesia, 2007)
One of the ways of producing butene compounds without relying on non-renewable resources involves the dehydration of n-butanol with the aid of acid catalysts. The dehydration of n butanol on molecular sieve 13 X catalyst has been undertaken in afvced bed, vertical glass pipe isothermal reactor. Reaction temperatures were varied between 300-450 °C. Reaction products were analyzed using a Gas Chromatograph (GC). The n-butanol dehydration was observed to have a reaction order of 1.95 with respect to n-butanol partial pressure, with an activation energy of 89.4 kJ/mol and an Arrhenius constant of 7.99 x 106 .To determine the effect of operating parameters (feed temperature, n-butanol flowrate, n-butanol to nitrogen feed ratio, and catalyst particle diameter), a simulation was undertaken based on the fvced bed, non adiabatic and non-isothermal reactor model. The reactor model used in the simulation was a 2- dimensional heterogeneous reactor. The validated model coefficient of correlation against the experimental data was very good, namely 0.98. Simulation results indicate that the increase in n-butanol concentration and feed temperature increase the conversion. Increase in catalyst particle diameter and feed flowrate decrease the conversion. The dehydration of n-butanol to butene is a mildly exothermic reaction. Therefore, to maintain an isothermal reaction condition, the reactor wall temperature may not exceed 10 °C below the feed temperature.Keywords: n-butanol dehydration, molecular sieve 13 X, simulation, fixed bed, kineticAbstrakSalah satu cara untuk mendapatkan senyawa butena tanpa mengandalkan sumber daya tak terbarukan adalah melalui dehidrasi n-butanol dengan bantuan katalis asam. Dehidrasi  n butanol pada katalis molecular sieve 13 X dilakukan di dalam reaktor unggun tetap terbuat dari pipa gelas tegak secara isotermal. Temperatur reaksi divariasikan antara 300 - 450" C. Komposisi produk dianalisa menggunakan Gas Chromatograph (GC). Dehidrasi n-butanol ini berorde 1,95 terhadap tekanan parsial n-butanol dengan nilai energi aktivasi 89,4 kJ/mol dan tetapan Arrhenius 7,99 x 106• Untuk mempelajari pengaruh  parameter  operasi  (temperatur umpan, laju alir n-butanol, rasio umpan n-butanol terhadap nitrogen, dan  diameter partikel katalis) terhadap konversi reaksi, distribusi produk, dan profil temperatur di sepanjang reaktor dilakukan simulasi dalam reaktor unggun tetap non adiabatik non isotermal berdasarkan data percobaan yang telah diperoleh. Model reaktor yang digunakan adalah model heterogen dua dimensi. Nilai koefisien korelasi model yang divalidasi dengan  data percobaan  menunjukkan harga yang baik yaitu 0,98. Hasil simulasi menunjukkan bahwa peningkatan konsentrasi n butanol atau temperatur umpan meningkatkan konversi. Peningkatan diameter partikel katalis atau peningkatan laju alir umpan, akan menurunkan konversi reaksi. Reaksi dehidrasi  n butanol menjadi senyawa buten merupakan reaksi yang sedikit eksoterm,  oleh karena itu untuk mempertahankan reaksi agar isotermal, temperatur dinding reaktor harus diusahakan tidak melebihi 10 °C di bawah temperatur umpan.Kata kunci: dehidrasi n-butanol, molecular sieve 13 X, simulasi, unggun tetap, kinetik